The Construction of Ecological Fiqh from the Perspective of Yusuf al-Qardhawi - Rosyidah, Umi; Al Banna, Ahmad Hasan (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
Environmental degradation is a global challenge that demands responses from various perspectives, including Islamic law. This article examines the construction of ecological jurisprudence according to Yusuf al-Qardhawi, a contemporary Islamic thinker who combines sharia principles with the urgency of environmental conservation. Through the approach of maqāṣid al-sharī'ah, al-Qardhawi places the preservation of the environment (ḥifẓ al-bī'ah) as a fundamental condition for the realization of the five main objectives of the Shari'ah: to protect religion, soul, intellect, descent, and property. This study uses a qualitative method with a normative and conceptual approach based on literature study. The results of the study show that al-Qardhawi offers a fiqh model that is not only normative, but also solutive and applicative, by emphasizing the importance of ecological responsibility as part of the mandate of the human caliphate. He also emphasized the urgency of the state's role in sanctioning environmental destruction through the ta'zīr mechanism. This thinking paves the way for fiqh renewal in responding to environmental issues more contextually and sustainably.